Examining Sidoarjo Transportation: Motor Vehicle Testing Services Analysis: Analisis Kualitatif Layanan Pengujian Kendaraan Bermotor Dinas Transportasi Sidoarjo - Mira Mutiara Syafira Bayuningtyas; Hendra Sukmana (Academia Open, 2023)
This study examines the process of implementing motor vehicle testing services in the Sidoarjo Transportation Department, East Java, using a qualitative approach. The aim is to describe and analyze the implementation process, supporting factors, and hindrances to motor vehicle testing services. The analysis reveals that the overall implementation of these services is relatively good, with positive outcomes in terms of communication, resources, disposition, and bureaucratic structure. Supporting factors include sufficient human resources and vehicle testing equipment, as well as community compliance with the Kir test program. However, budget constraints resulting from the diversion of resources to tackle the Covid-19 pandemic have hindered the program's expansion, particularly in terms of parking area regulations on the East Ring highway. The findings suggest the need for effective resource allocation and improved infrastructure planning to address bottlenecks and ensure smooth motor vehicle testing services, ultimately enhancing road safety and efficiency. Highlights: Efficient implementation: The study examines the process of motor vehicle testing services in Sidoarjo's Transportation Department, highlighting its relative effectiveness. Supporting factors: Adequate human resources and vehicle testing equipment contribute to the successful implementation of the testing program. Budget constraints and obstacles: Limited budget due to the diversion of resources for COVID-19 management, along with challenges in expanding parking areas, pose hindrances to the program's smooth execution. Keywords: Motor vehicle testing, Sidoarjo Transportation Department, Qualitative analysis, Implementation process, Supporting factors